PENGARUH MODAL INTELEKTUAL DAN MODAL KERJA TERHADAP TINGKAT PENGEMBALIAN SAHAM DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan yang Masuk dalam Penghitungan Indeks KOMPAS100 tahun 2014-2015) - Rindi Minanti Trifatni; Yusralaini Yusralaini; Hariadi Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The aims of this research are to examine: (1) the effect of intellectual capital and working capital to profitability; (2) the effect of intellectual capital and working capital to stock return; (3) ) the effect of profitability to stock return; (4) the effect of intellectual capital and working capital to stock return with profitability as a intervening variables. The population of this research is the companies that included in the index calculation KOMPAS100 in the period of 2014-2015. By using purposive sampling there are 70 companies that fulfil the criterias. The research data was analyzed by using multiple regression analysis and path analysis. Path analysis was used to examine indirect effect between independent variables and dependent variables. The research data was used SPSS version 17.Based on the result, it can be concluded that; (1) intellectual capital has the significant effect on profitability; (2) working capital has the significant effect on profitability;(3) intellectual capital has no effect on stock return; (4) working capital has no effect on stock return; (5) profitability has the significant effect on stock return; (6) profitability could mediated the relationship between intellectual capital and stock return; (7) profitability could mediated the relationship between workin capital and stock returnKeywords: Stock Return, intellectual capital, working capital, profitability